Régimen sensible corporizado : las prácticas corporales reflexivas en Medellín desde 1980 (2014)
ABSTRACT: The following article studies the dynamic configuration of an Embodied Sensitive Regime unveiled through Reflexive Body Practices deployed in Medellin since the 1980s. Using a genealogical and ethnographic approach, the materialsymbolic ground of these practices is unveiled, as well as their underlying modes of appropriation and consumption, constituting traits of an esthetic-political regime that uses the embodied sensory experience to stimulate processes of subjectivation, while producing an order of perception in the recent history of Medellin. This regime motivates processes of subjectivation and control that pass through forms of perception and the body. The construction of sensitive bodies is a process that combines forms of individual autonomy with forms of life government related to welfare, social urbanism, productivity and health. The contribution to the study of the history of the body in Medellín, is to go beyond discourse to analyze bodily practices as performances, including the experience of practitioners as a way to show the constitution of corporeality in the production of knowledge and in the individual and social experience.